A short history of western political thought - Spellman, W. M. (Houndmills, Basingstoke, Hampshire : Palgrave MacMillan, 2011)
'This book provides a highly accessible narrative survey of political thought over the past two millenia. Exploring many key ideas in the Western tradition, it begins with the classic political thought of the ancient Greeks, it moves through the medieval and early Christian views of politics, and concludes by exploring the modern re-interpretation of political life'--Provided by publisher.
'This book provides a highly accessible narrative survey of political thought over the past two millenia. Exploring many key ideas in the Western tradition, it begins with the classic political thought of the ancient Greeks, it moves through the medieval and early Christian views of politics, and concludes by exploring the modern re-interpretation of political life'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Political science -- History; Political science -- Philosophy -- History; Civilization, Western